2016
DOI: 10.1155/2016/9146378
|View full text |Cite
|
Sign up to set email alerts
|

Systems Pharmacology Based Study of the Molecular Mechanism of SiNiSan Formula for Application in Nervous and Mental Diseases

Abstract: Background. Mental disorder is a group of systemic diseases characterized by a variety of physical and mental discomfort, which has become the rising threat to human life. Herbal medicines were used to treat mental disorders for thousand years in China in which the molecular mechanism is not yet clear. Objective. To systematically explain the mechanisms of SiNiSan (SNS) formula on the treatment of mental disorders. Method. A systems pharmacology method, with ADME screening, targets prediction, and DAVID enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 59 publications
(58 reference statements)
0
13
0
Order By: Relevance
“…SPT and FST are usually applied to rats to evaluate depression-like behavior and antidepressant effect. The effect of SNS on mental disorders and chronic stress-related diseases, such as depression, has been already demonstrated in some studies, but age specificity was not mentioned (27, 28). Our results indicated that young and adult MS rats exhibited anhedonia during SPT as shown by the reduced sucrose consumption and behavioral despair during FST as shown by augmented immobility time.…”
Section: Discussionmentioning
confidence: 99%
“…SPT and FST are usually applied to rats to evaluate depression-like behavior and antidepressant effect. The effect of SNS on mental disorders and chronic stress-related diseases, such as depression, has been already demonstrated in some studies, but age specificity was not mentioned (27, 28). Our results indicated that young and adult MS rats exhibited anhedonia during SPT as shown by the reduced sucrose consumption and behavioral despair during FST as shown by augmented immobility time.…”
Section: Discussionmentioning
confidence: 99%
“…SNS can soothe the liver, remove internal heat, strengthen the spleen, and nourish the blood. Furthermore, it has been clinically applied for the improvement of mental diseases, including depression and other conditions (Shen et al, 2016). Although SNS has certain clinical effects in the treatment of depression (Wang et al, 2009), the lack of rigorous experimental research counteracts the unique advantages of TCM, which seriously hinders its promotion and application worldwide.…”
Section: Highlights Introductionmentioning
confidence: 99%
“…It is noteworthy XYS has been approved as a non-prescription formula by State Food and Drug Administration (SFDA), which reinforce validity about the safety of XYS. The explanation of the encouraging safety might be that the multi-target effect of herbal preparations may produce relatively low concentration of active ingredients [40]. As we mentioned above that majority of women with PMS preferred non-pharmacological interventions to HRT [17] [18] [19], XYS can be recommended for its distinguished safety.…”
Section: Discussionmentioning
confidence: 99%